Sinnbilder in der Sintflutgeschichte - GERÉB, Zsolt (Studia Universitatis Babeș-Bolyai Sacra Scripta, 2026)
The author of the history of flood would like to answer the old question of humanity about the connection between the natural catastrophe and God`s will. He tries to give an answer by means of a narrative or by the help of symbols, respectively. The task of the interpreter consists in clarifying the truth that generated the symbols. Our starting point in our analysis is that one cannot study the story isolated from the whole biblical text. By visualizing the narrative the author intends to express the theological thinking that the natural catastrophe cannot be looked upon as a fateful happening, but as upon God`s instrument to express his own creative will in Salvation History.